Some Considerations on Conceptual Issues in History of Economic Thought - Chaparro, Germán Raúl (Sociedad y Economía, 2021)
This paper aims to vindicate the importance of the teaching and practice of the History of Economic Thought, as a medium that offers a general and integrated view of the field of Economics that favors the advancement of economic theory. To do so, it is proposed to recover the matrix method. It is concluded that this alternative has the potential to contribute to the development of high-level cognitive skills and critical thinking.